Interactions of Black and Green Tea Water Extracts with Antibiotics Activity in Local Urinary Isolated Escherichia coli - Passat, Dimah N (Al-Nahrain Journal of Science, 2012)
A total of 17 Escherichia coli isolates were collected from urine specimens of patients with urinary tract infection. Antibiotics sensitivity test indicated that amikacin followed by chloramphenicol and ciprofloxacin are the most effective antibiotics. The isolates showed multidruge resistant, nine isolates were resistant to 11-15 antibiotics, 3 were resistant to 16-20 antibiotics and 5 were resistant to 21-25 antibiotic. Two isolates were selected, the first (ED1) was resistant to (22) antibiotics while the second isolate (ED2) was resistant to (14) antibiotics (out of 25). Minimum inhibitory concentration (MIC) of the black and green tea water boiled extracts were determined towards (ED1,ED2).Results showed that MIC of black tea extract was 150 mg\ml (ED1) and 100mg\ml (ED2),and the MIC of the green tea extract was 275 mg\ml (ED1) and 250mg\ml(ED2).The interaction of Sub-MIC of both extracts with antibiotics showed that black tea has synergetic effect with gentamycin, tobramycin, chloramphenicol and cefodizim, and antagonistic effect with: streptomycin, amikacin, tobramycin, kanamycin, piperacillin, cefepim, nalidixic acid, and azithromycin .Green tea has synergistic effect with : chroramphenicol, amoxicillin, azithromycin, ciprofloxacin and cefodizim and antagonistic effect with: amikacin, streptomysin, tobramycin gentamicin ,kanamycin, cefepim, azithromycin, piperacillin. This study suggests that a combination of black and green tea water extracts with some antibiotics in vitro has synergistic or antagonistic effect on urinary tract E.coli isolates.